Business Philosophy Education and Improving Critical Thinking Skills of Business Students - Azzaakiyyah, Hizbul Khootimah; Wanof, M. Indre; Suherlan, Suherlan; Fitri, Wahyuni Shalatan (ADMAN: Journal of Contemporary Administration and Management, 2023)
Business Philosophy Education is a discipline that aims to assist individuals in understanding the meaning and values of business, as well as helping them to develop critical thinking skills. Critical thinking ability is very important in the business world because it allows individuals to make the right decisions that are beneficial to the company. However, there are still many business students who lack adequate critical thinking skills. This study aims to explore the influence of Business Philosophy Education on improving the critical thinking skills of business students. This research is qualitative in nature. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study concluded that Business Philosophy Education has an important role in improving business students' critical and ethical thinking skills in dealing with complex and ambiguous business situations. Through this education, business students can gain a deeper understanding of the philosophical principles underlying business practices, so that they can make more socially and environmentally responsible decisions.